The budget constraint in the governance of organizations - Bruno Dallago (Transformation, Integration and Globalization Economic Research (TIGER), 2007)
The paper suggests a partial solution to the disjunction between the institutional environment and the institutions of governance by considering the budget constraint. This approach is put in the perspective of the comparative analysis of economic organizations as discrete structural alternatives. The budget constraint presents a whole range of alternative values that are distinct by different transaction costs that organizations meet. Following different values of budget constraint, bounded rationality and opportunism are allocated to alternative uses and asset specificity takes different forms. This approach requires that the discriminating alignment solution considers the prevailing value of the budget constraint, which opens the need for a comparative perspective on efficacious organizational governance. A second level of governance is corporate governance. The debate over corporate governance is centered around decision-making power and the existence of quasi-rents that organizations produce. Given different values of the budget constraint, the definition of what are efficacious systems of decision-making power and appropriation of quasi-rents are distinct in the shareholder value and the stakeholder interest paradigms.
Keywords: D23; G34; L22; P12; 330; Budgetrestriktion; Corporate Governance; Rententheorie